Gaseous cavitation in transmission line - Yeo, Wei Jian (2019)
A comprehensive study on gaseous cavitation in transmission lines will be presented. A model will be developed to simulate and forecast the effect of cavitation. Previous cavitation models including the “column separation model” as well as the “two-phase homogeneous equilibrium vaporous cavitation model” will be studied and compared with gaseous cavitation model. The latter predicts better accuracy in degree of cavitation due to the inclusion of dissolved gas components. The model will be developed by deriving two governing equations. The governing equations will then be simplified into four ordinary differential equations using the method of characteristics. Finite difference equations can be obtained by using integration, which will used to compute a computer program using Fortran programming. With the use of the program, the result from the proposed model will be compared to the results from the previous models and the experiment conducted by Sanada et al. The proposed model result has shown close correspondence with the experimental data conducted by Sanada et al, therefore verifying that the model can produce accurate prediction of vaporous and gaseous cavitation in transmission line.